(untitled) (Perner’s Contacts, 2019)
This paper investigates the crack driving force in the wheel-rail contact using a finite element model. The presented work determines significant model variables such as an effect of the loading type, friction coefficients, cyclic plasticity and the number of the integration contour on the crack driving force and lays the foundation for the further development of the model and computational schemes.